Immunogenicity and protective efficacy of a prototype pneumococcal bioconjugate vaccine. Issue 42 (6th October 2022) - Aceil, Javid; Paschall, Amy V.; Knoot, Cory J.; Robinson, Lloyd S.; Scott, Nichollas E.; Feldman, Mario F.; Harding, Christian M.; Avci, Fikri Y.
Highlights: Bioconjugation is an effective alternative for chemical conjugate vaccine design. CPS8-EPA iGTcc induces robust immune response regardless of biological sex or dosage. CPS8-EPA iGTcc protects mice against lethal intranasal or sepsis ST8 challenge. Abstract: Capsular polysaccharides (CPSs), with which most pathogenic bacterial surfaces are decorated, have been used as the main components of glycoconjugate vaccines against bacterial diseases in clinical practice worldwide. Pneumococcal conjugate vaccines (PCVs) are administered globally to prevent invasive pneumococcal disease (IPD). While PCVs have played important roles in controlling IPD in all age groups, their empirical, and labor-intensive chemical conjugation yield poorly characterized, heterogeneous, and variably immunogenic vaccines, with poor immune responses in high-risk populations such as the elderly and patients with weak immune systems. We previously developed a method that bypasses the dependency of chemical conjugation and instead exploits prokaryotic glycosylation systems to produce pneumococcal conjugate vaccines. The bioconjugation platform relies on a conjugating enzyme to transfer a bacterial polysaccharide to an engineered carrier protein all within the lab safe bacterium E. coli . In these studies, we demonstrate that a serotype 8 pneumococcal bioconjugate vaccine is highly immunogenic and elicits functionally protective anti-serotype 8 antibody responses. Specifically, using multiple models we show that mice immunized with multiple doses of a serotype 8 bioconjugate vaccine elicit antibody responses that mediate opsonophagocytic killing, protect mice from systemic infection, and decrease the ability of serotype 8 pneumococci to colonize the nasopharynx and disseminate. Collectively, these studies demonstrate the utility of bioconjugation to produce efficacious pneumococcal conjugate vaccines.